Enhanced Thermal Conductivity of Polymer Composite by Adding Fishbone-like Silicon Carbide - Juncheng Xia (MDPI AG, 2021)
The rapid development of chip technology has all put forward higher requirements for highly thermally conductive materials. In this work, a new type of material of Fishbone-like silicon carbide (SiC) material was used as the filler in a polyvinylidene fluoride (PVDF) matrix. The silicon carbide/polyvinylidene fluoride (SiC/PVDF) composites were successfully prepared with different loading by a simple mixing method. The thermal conductivity of SiC/PVDF composite reached 0.92 W m−1 K−1, which is 470% higher than that of pure polymer. The results show that using the filler with a new structure to construct thermal conductivity networks is an effective way to improve the thermal conductivity of PVDF. This work provides a new idea for the further application in the field of electronic packaging.